1991
DOI: 10.1148/radiology.179.3.2027970
|View full text |Cite
|
Sign up to set email alerts
|

Exertional muscle injury: evaluation of concentric versus eccentric actions with serial MR imaging.

Abstract: Eccentric muscular actions involve the forced lengthening or stretching of muscles and tend to produce exertional injuries. This study used magnetic resonance (MR) imaging to serially evaluate muscles in five healthy, untrained subjects who performed exhaustive biceps exercise by doing isolated eccentric and concentric actions with a dumbbell. Symptoms were assessed, and T2-weighted images of the arms were obtained before exercise and 1, 3, 5, 10, 25, 40, 50, 60, and 80 days after exercise. Statistically signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
102
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(104 citation statements)
references
References 0 publications
2
102
0
Order By: Relevance
“…These changes include a prolonged decline in muscle strength, a shift in the optimal joint angle to produce peak torque to longer muscle lengths, changes in the relaxed elbow joint angle that are indicative of increased passive muscle tension, and an increase in muscle soreness 2 days after the exercise. Changes in these and other markers of muscle damage are not observed after concentric exercise, which produces a short-lasting decline in muscle strength with minimal muscle damage (10,18,55). The decline in muscle strength after concentric exercise primarily results from metabolic fatigue in the muscle (19) with recovery of strength within 2 h (18,26,38).…”
Section: Muscle Damage and Neuromotor Performance After Eccentric Exementioning
confidence: 99%
“…These changes include a prolonged decline in muscle strength, a shift in the optimal joint angle to produce peak torque to longer muscle lengths, changes in the relaxed elbow joint angle that are indicative of increased passive muscle tension, and an increase in muscle soreness 2 days after the exercise. Changes in these and other markers of muscle damage are not observed after concentric exercise, which produces a short-lasting decline in muscle strength with minimal muscle damage (10,18,55). The decline in muscle strength after concentric exercise primarily results from metabolic fatigue in the muscle (19) with recovery of strength within 2 h (18,26,38).…”
Section: Muscle Damage and Neuromotor Performance After Eccentric Exementioning
confidence: 99%
“…A direct relationship among T 2 increase, CK blood level (33, 41), and lactate dehydrogenase activity (41) has been reported in humans during the days following an eccentric exercise, hence indicating that T 2 changes could quantitatively illustrate the damage severity. It has been shown that T 2 increases immediately after a concentric exercise (33, 50) and can remain elevated for a period of 3 mo (43,59). MRI has been used to serially assess skeletal muscle of DMD patients.…”
mentioning
confidence: 99%
“…When quantified on a pixel-by-pixel basis, the areas of muscle demonstrating increased T2 after electrically stimulated exercise [via electromyostimulation (EMS)] (2, 7) have been found to correlate to torque production, allowing T2 magnetic resonance (MR) images to be used as a relative index of muscle activation during exercise (37). Subsequent to eccentric exercise, a delayed increase in the T2 has been observed that peaks 2-6 days after exercise (12,39). This delayed increase correlates to histological assessment of muscle injury in both humans (30) and animals (26) and with changes in other traditional markers of muscle injury such as soreness, serum creatine kinase levels, and isometric force loss (7,12,38).…”
mentioning
confidence: 99%
“…It is well documented that eccentrically exercised muscles demonstrate a delayed increase in T2 that peaks several days after exercise and persists for several weeks (12,39). Debate remains as to the mechanism responsible for this prolonged increase in relaxation time that persists long after other markers of injury have returned to baseline levels.…”
mentioning
confidence: 99%